Vaccination strategies to combat an infectious globe: Oral cholera vaccines - Rosa M López-Gigosos; Elena Plaza; Rosa M Díez-Díaz; Maria J Calvo (Journal of Global Infectious Diseases, 2011)
Cholera is a substantial health burden in many countries in Africa and Asia, where it is endemic. It is as well responsible for ongoing epidemics in sub-Saharan Africa which are becoming greater in terms of frequency, extension, and duration. Given the availability of two oral cholera vaccines and the new data on their efficacy, field effectiveness, feasibility, and acceptance in cholera-affected populations and in travelers, these vaccines should be used in endemic areas, in travelers for these areas and should be considered in areas at risk for outbreaks. The two vaccines currently available in worldwide are: (1) The killed oral vaccine (Dukoral, licensed by SBL-Sweden to Crucell-Holland) is recommended since 1999 by WHO and consists of a mixture of four preparations of heat or formalin killed whole cell Vibrio cholera O1 (Inaba and Ogaba serotypes, and classical and El Tor biotypes) that are then added with purified recombinant cholera toxin (CT) B subunit. Because CT cross-reacts with Escherichia coli LT the vaccine also provides short-term protection against ETEC (enterotoxigenic E. coli) which is of added benefit for travelers. It is available in more than 60 countries. (2) A bivalent O1 and O139 whole cell oral vaccine without CT B subunit (Shanchol) has been lately developed in Vietnam (licensed by VaBiotech-Viet Nam to Shantha Biotechnics-India. It is available in India and Indonesia. A structured search of papers in PubMed and reports on cholera vaccines by WHO and CDC, as well as critical reading and synthesis of the information was accomplished. Inclusion criteria were defined according to reports quality and relevance.